The Architecture of Project-Based Learning in the Supplementary Vocational Education System in a Higher Education; International Journal of Emerging Technologies in Learning (iJET); Vol. 15, No. 4 - Lizunkov V. G. Vladislav Gennadyevich (2020, 2020)
Title screen